Implementación de un plan de marketing para la funeraria de la cooperativa “Cacpe Zamora” en la ciudad de Zamora período 2016-2020 - Ortega Rodríguez, Diego Fernando (2016)
To carry out this investigation, it is general objective: to develop a marketing plan for the funeral of the cooperative "CACPE Zamora" in the city of Zamora 2016-2020 period, where different methods such as was used; Historical, deductive, inductive, statistical and analytical techniques and direct observation, interview and survey manager both internal customers (5 employees) as a sample to external customers (395 customers). The study began with the situational analysis, in which both the internal and external environment was discussed. In the external environment factors such as political, legal, economic, social, cultural, technological and Porter's five forces were analyzed, obtained the EFE matrix, where was evident as OPPORTUNITIES political stability, implementation of technological resources, financial facility, demand of service under financial promotions, and barriers to entry for new companies with a score of 2.83 results indicating that the overall external strategic position of the company is above average. For analysis of the internal environment we proceeded with gathering information through research techniques; Thus interviewed the manager of the funeral home, in addition to 5 employees and a sample of 394 customers were surveyed. With the information gathered we proceeded to build the EFI Matrix, where a weighted score of 2.43 which means that the funeral is fairly strong internally but should improve those weaknesses to be solidly strong determined. Then we proceeded to the development of the SWOT matrix, where it was noted that currently the funeral home does not have a marketing plan that will improve the care and customer service, taking advantage of the strengths and opportunities available to, and correct their weaknesses to strengthen the implementation of strategies to address threats. That is why in the MATRIX HIGH IMPACT at the junction of the variables were 4 strategic objectives, such as: perform an advertising and promotional plan to help achieve proper positioning of the company in the market and therefore satisfaction to partners or customers of the company, implement an internal control program to competition in order to keep information on market developments, make a training plan to achieve the performance of human talent in the business, develop an internal motivation program and incentives to employees of the company trying to achieve capture maximum performance of each of them, which are broken down in the proposed development of strategic objectives and in conclusion the budget required for the implementation of operational plans is of $ 1,895.00; it is estimated that this investment will consolidate the image of the funeral in the market and thus improve profitability. That is why what the funeral of the Cooperative CACPE Zamora is recommended, apply the proposed marketing plan, applying strategic market designs and thus improve the current situation of it.